Cicero’s De legibus: Environment and the Symbolic Value of locus - Tsouni, Georgia (Ciceroniana On Line, 2023)
The prologues to the first and second books of Cicero’s De legibus uniquely represent a rural environment as the setting of the discussion. While Cicero has a Platonic model in mind, I discuss how his depiction of the rural environment in the De legibus goes beyond its Greek model. This is visible both in the way the surrounding environment provides the context for authorial remarks on the genre and dialogical style of the text but, furthermore, in the way the rural landscape bears symbolic value which links it directly to Roman ancestral values and exempla. As such it may also be read as a counterpart to the city landscape of Athens, a locus related to theoretical virtue and intellectual exempla, which is depicted in De finibus 5. The symbolic investment of rural environment aims at underlining the “practicability” and superiority of Rome’s traditional constitution but also Cicero’s own role as a defender of the res publica.